Understanding of Spirituality among Healthcare Professionals at Chris HaniBaragwanath Academic Hospital: A Social Work Perspective. (1st January 2016) - Nkomo, Thobeka S.
Abstract: Everything concerning the spirit or soul has been the domain of the church or religious organisations. The awakening on spirituality can be traced back to the latter decades of the 20th century. Now it is picking up momentum and it cannot be denied anymore. Literature has indicated the importance of including spirituality as a means of assisting people to cope during trying times. The primary aim of this paper is to explore the views of healthcare professionals on the subject of spirituality. In this research, a qualitative research approach, which aims at understanding social interaction and experiences from the perspective of insiders, was used. The research adopted the exploratory design which focused on gaining insight into the views of the participants within and under the researched field.